Investigating the outcome of the initial assessment at a national transgender health service: is it time to review the process? - Jones, Bethany Alice; Brewin, Nicola; Richards, Christina; Van Eijk, Marnix; Stephenson-Allen, Alex; Arcelus, Jon (Taylor & Francis, 2017)
Background: Globally there is a lack of a standardised assessment process prior to the initiation of gender affirming medical interventions and consequently there is a discrepancy in this process among different transgender health services. Aim: The main objective of this study is to investigate the outcome of the initial assessment process at a national transgender health service. Method: The outcome of people over the age of 17 years, assessed at a large national transgender health service in the United Kingdom during a two year period was categorised into: 1) recommendation for cross-sex hormone treatment, or: 2) no recommendation for cross-sex hormone treatment. In addition, 200 case notes were reviewed in order to investigate the level of agreement between the two clinicians involved in the assessment process. Results: During the study period a total of 617 people completed their assessment at the service. Following assessment 380 (61.6%) patients were recommended for cross-sex hormone treatment, leaving 237 (38.4%) patients who required a longer assessment period or were discharged. The factors associated with being recommended for cross-sex hormone treatment were: having socially transitioned, not smoking, having initiated cross-sex hormones prior to assessment, being older, and assigned male at birth. Out of the 200 case notes reviewed, agreement between assessor 1 and 2 (3 months apart) was found in 88 % (n= 176) of the cases. Discussion: Although the results of the study may not be generalizable to other international centres, questioning the assessment process and the role of the assessors is important to ensure treatment is offered in a timely and efficient manner. The findings from this study suggest that the routine inclusion of two assessors needs to be reviewed.